On inner voice, free indirect style, and lyric. Issue 6 (3rd June 2021) - Houen, Alex
ABSTRACT : In this essay, I examine how both Claudia Rankine in Citizen and Ben Lerner in The Topeka School present innovative modes of voicing and listening by using free indirect style to relate inner voice and social discourse. Discussing these literary works is only part of my focus, though, for the following reason: theorists of free indirect style haven't tended to consider that style in terms of how a person relates to their own inner voice, nor have they related the style to lyric poetry; similarly, theorists of lyric haven't related lyric to free indirect style; therefore, innovative approaches such as Rankine's and Lerner's call for a reconsideration of the theories and criticism around inner voice, free indirect style, and lyric, and that reconsideration forms a major part of this essay.